Return to sports following shoulder injury: Clinical evaluation, isokinetic, and functional testing - Fontánez, R.; De Jesus, K.; Frontera, W. R.; Micheo, W. (Current Sports Medicine Reports, 2023)
The shoulder is commonly injured in overhead sports. This is associated with a high degree of mobility at the expense of stability, sports specific demands, high volume or intensity of practice and competition, biomechanical deficits, and poor technique. Following injury, the return to competition process includes nonsurgical or surgical treatment, comprehensive rehabilitation, and a structured return to sports program. The return to sports continuum is divided into phases which include return to practice of the sport, return to competition at a lower level or with reduced performance, and return to expected performance. Components of the return to sports decision include clinical evaluation of physical and psychological readiness, measurement of muscle strength using isokinetic tests, evaluation of overhead functional tasks, and progression in a supervised interval throwing program. The evidence for the effectiveness of return to sports programs following shoulder injury is limited but evolving and is an area that will merit continued investigation.